(untitled) (Iranian Journal of Kidney Diseases, 2014)
Salmonella species are a rare cause of urinary tract infection in children. They are associated with a high incidence of structural abnormalities or immunosuppressive status. We report the case of a healthy 7-year-old boy with pyelonephritis due to Salmonella group. He did not have a history of recent gastroenteritis.